Editorial: Working with Uncertainty (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
A reflection on the crises and the uncertainties of our times should lead scholars to realize that uncertainty is a part and parcel of educating and learning, of knowledge-making and application–of our role in society. It is our job to figure things out, to grapple with uncertainty. It is our responsibility to prepare future generations to navigate uncertainty, or navigate the world in the face of uncertainty. It is in the very nature of knowing and sharing knowledge to deal with uncertainty, to entertain ambiguity, to explore possibilities, to be open minded. Asking questions, posing hypotheses, engaging diverse perspectives, even tolerating contradictions–these are all tools of our trade. It is also part of our profession to do what we can when we do not know about every aspect of a situation, to contribute our bit even when we know it means little, and to hold judgment when we seem to be right.